MITIGASI BENCANA MENGGUNAKAN PETA FAKTOR KEAMANAN LIKUIFAKSI BERDASARKAN CONE PENETRATION TEST (STUDI KASUS ITERA) - Ahmad Yudi; Sayed Ahmad Fauzan; Nugraha Bintang Wirawan (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Institute Technology of Sumatera (ITERA) located on Sumatera Island, take place on Lampung Selatan (South Lampung. As the coastal region, Lampung Selatan dominated by the sandy soil which allows the possibility of the Liquifaction. The objectives of this research is to mitigate the Liquifaction with analyze using Liquifaction of the safety factor map under the deterministic method. In order to establish the development of Institute Technology of Sumatera (ITERA, this research expected can be used as the consideration to mitigate the damage in relation with the site condition. Deterministic method is the ratio comparison of the Cyclic Resistant Ratio (CRR) and the Cyclic Stress Ratio (CSR) effected by the earthquakes. Cyclic Stress Ratio (CSR) depends on the depth of the soil layer, total vertical pressure, effective vertical pressure, earthquake’s magnitude and the peak ground acceleration. Meanwhile, the Cyclic Resistance Ratio (CRR) calculated by the correlation of the empirical result of CPT. The safety factor value analyzed by the comparison value of CSR and CRR that pointed on 12 CPT location. In result, take the test location on ITERA, it is known that the safety factor in this site is on the safe zone and have been described on the color zone on the map as the disaster mitigation.